2014
DOI: 10.1177/1090820x14545984
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Prophylactic Antibiotics in Outpatient Plastic Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“… 31 33 Several authors have argued that prophylactic antibiotics are not necessary in much of plastic surgery. 33 36 …”
Section: Resultsmentioning
confidence: 99%
“… 31 33 Several authors have argued that prophylactic antibiotics are not necessary in much of plastic surgery. 33 36 …”
Section: Resultsmentioning
confidence: 99%
“…According to a 6-year study by Baran et al,17 there was no significant difference in infection rates between a group of patients treated with antibiotics and a group not treated with antibiotics. Anigian et al18 also demonstrated that postoperative administration of antibiotics did not result in lower morbidity rates than preoperative administration alone, and Hunter et al19 recommended the discontinuation of prophylactic antibiotics within 24 hours after surgery as part of the recommendations for prophylactic antibiotic use in plastic surgery. Conversely, there are several studies demonstrating the benefits of postoperative antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Anigian et al 9 show that difference in timing of prophylaxis did not affect their complication rate, and they debate the effectiveness for prophylaxis in clean cases. Hsu et al analyzed the studies looking at breast and other elective surgery—despite the use of implants and nipple contamination risk, there was a minimal difference in SSI in breast augmentations when antibiotic prophylaxis was used (0%–0.7%); however, in clean-contaminated cases such as rhinoplasty, there was a significant difference between prophylactic and nonprophylactic group (0%–8.9%).…”
Section: Discussionmentioning
confidence: 99%
“…1 Through records and codes, Centers for Medicare and Medicaid Services quality indicators show that smaller office-based suites and ambulatory surgical centers perform better than hospitals 9,10 ; yet do not provide adequate information or basis to compare elective aesthetic surgery infection rates. Even national databases that include cosmetic surgery data, such as the National Surgical Quality Improvement Program or Tracking Operations and Outcomes for Plastic Surgeons, are still difficult to analyze because certain variables are unsearchable, are unspecific input narrows specificity by procedure, and can include subjective details during input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation